(untitled) (American Journal of Research in Humanities and Social Sciences, 2022)
This article talks about the possibilities of developing ethnotourism in Uzbekistan (as an example of the activities of the National Cultural Center of the Arab Diaspora). Based on archival data, the author studied and analyzed specific aspects of the possibilities of developing ethnotourism in Uzbekistan (as an example of the activities of the national cultural center of the Arab diaspora) on the basis of available scientific literature.